Molecular cloning and overexpression of stem bromelain from Ananas comosus in Kluyveromyces lactis - Ramli, Aizi Nor Mazila (2017)
There are many cultivar of pineapple, A. comosus available around the world. Morris, N36 and Sarawak cultivar use throughout this work was amongst cultivars grown in Malaysia. Proteolytic enzyme found in pineapple plant, is known as bromelain. The enzyme catalyzes the breakdown of peptide bond from the polypeptide chain by hydrolysis. Nowadays, numerous therapeutic benefits have been claimed for bromelain. Bromelain, belonging to papain family, is a glycosylated single chain protein consists of cysteine proteinases. A gene encoding bromelain from pineapple (Ananas comosus) was isolated from Morris cv. using the Reverse Transcriptase (RT)-Polymerase Chain Reaction (PCR) techniques. The isolated gene was successfully expressed in the E. coli. Analysis of the nucleotide sequence revealed the presence of bromelain coding sequence, I ,056 base pair (bp) which encodes 302 amino acid. Up to now, the three-dimensional (3D) structure ofbromelain remained to be elucidated. The comprehensive information about the thorough structural organization ofbromelain is vital for therapeutical application and in understanding their role in the cell and in other related molecular mechanisms. Therefore the purpose of this research work is to screen for bromelain from different cultivars of A. comosus followed by bromelain sequence analysis and accurate 3D structure determination using bioinformatics tools. This research study will provide the information of the bromelain concentration in different cultivars of A. comosus. In addition, details of bromelain sequence importance for therapeutical application followed by the accurate predicted structure of bromelain from A. comosus that can be used to defme the molecular catalysis mechanism ofbromelain will be provided.